Manipulating dislocation nucleation and shear resistance of bimetal interfaces by atomic steps. (July 2016) - Zhang, R.F.; Beyerlein, I.J.; Zheng, S.J.; Zhang, S.H.; Stukowski, A.; Germann, T.C.
Abstract: By means of atomistic simulations and interface dislocation theory, the mechanism of dislocation nucleation and shear resistance of various stepped fcc/bcc interfaces are comparatively studied using the Kurdjumov-Sachs (KS) Cu/Nb interface as a prototype. It is found that the introduction of atomic steps at the flat Cu111/110Nb KS interface does not change the most preferred slip systems, but influences the nucleation sites at the interface during tension loading, indicating that the flat and stepped interfaces possesses comparable energetic barriers for dislocation nucleation. During shear loading, the steps may significantly enhance the resistance to interface sliding by propagating partial dislocations that facilitate the emission and growth of parallel twins via cross slip. When the parallel twins are not favored or are hindered, the interface sliding will dominate in a "climbing peak-to-valley" manner. These results provide an effective pathway to solve the trade-off dilemma between dislocation nucleation and interface sliding by appropriately manipulating atomic steps at the flat interface in the design of high-strength metallic materials. Graphical abstract: